Acoustic journal bearing – Performance under various load and speed conditions. (October 2016) - Stolarski, T.A.; Gawarkiewicz, R.; Tesch, K.
Abstract: The paper presents results of experimental testing aiming at finding out what effect system of piezo-electric actuators (PZTs) attached to an aerodynamic journal bearing has on the magnitude of shaft׳s motion within the bearing operating at specified speed and load. The results clearly demonstrate effectiveness of PZTs in mitigating the shaft׳s motion thus contributing to the increased stability of the bearing. This stabilizing effect is especially pronounced for lightly loaded bearing running at speed. Three bearings, each having a different geometry, were tested and their dynamic performance recorded using fast response data acquisition system. Highlights: Practical feasibility of an acoustic air bearing is demonstrated. Bearing's geometry is vital for the acoustic levitation effect. Experimental results validate effectiveness of acoustic levitation. Dynamic performance of tested bearings is ranked.